Multiproduct retailing and consumer shopping behavior: The role of shopping costs (2020)
We empirically examine the role of shopping costs in consumer shopping behavior in a context of competing differentiated supermarkets that supply similar product lines. We develop and estimate a model of demand in which consumers can purchase multiple products from multiple stores in the same week, and incur transaction costs of dealing with supermarkets. We show that a similar model without shopping costs predicts a larger proportion of multistop shoppers and overestimates own-price elasticities and product markups. Further, we use our model along with a model of competition between supermarkets to study two practices that are commonly used by supermarkets: product delisting and loss-leader pricing. We show that the presence of shopping costs makes product delisting less profitable whereas it makes loss-leader pricing more profitable compared to a context in which consumers do not incur shopping costs. © 2019 Elsevier B.V.